The Emerging Potential of Multi-Ion Radiotherapy - Ebner, Daniel K.; Frank, Steven J.; Inaniwa, Taku; Yamada, Shigeru; Shirai, Toshiyuki (Frontiers in Oncology, 2021)
Research into high linear energy transfer (LET) radiotherapy now spans over half a century, beginning with helium and deuteron treatment in 1952 and today ranging from fast neutrons to carbon-ions. Owing to pioneering work initially in the United States and thereafter in Germany and Japan, increasing focus is on the carbon-ion beam: twelve centers are in operation, with five under construction and three in planning. While the carbon-ion beam has demonstrated unique and promising suitability in laboratory and clinical trials toward the hypofractionated treatment of hypoxic and/or radioresistant disease, substantial developmental potential remains. Perhaps most notable is the ability to paint LET in a tumor, better focusing damage delivery within the most resistant areas of disease. While protons and carbon-ions can be used in this manner, the technique may ultimately be limited by the physical properties of the beams themselves. A carbon-capable synchrotron is able to provide irradiation with other heavy-ions; helium and oxygen are prime candidates. Each ion varies in LET distribution, and so a methodology combining the use of multiple ions into a uniform LET distribution within a tumor may allow for even greater treatment potential in radioresistant disease.